If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -1(1 + -1x) = 5x + -5(1 + -1x) -4x + (1 * -1 + -1x * -1) = 5x + -5(1 + -1x) -4x + (-1 + 1x) = 5x + -5(1 + -1x) Reorder the terms: -1 + -4x + 1x = 5x + -5(1 + -1x) Combine like terms: -4x + 1x = -3x -1 + -3x = 5x + -5(1 + -1x) -1 + -3x = 5x + (1 * -5 + -1x * -5) -1 + -3x = 5x + (-5 + 5x) Reorder the terms: -1 + -3x = -5 + 5x + 5x Combine like terms: 5x + 5x = 10x -1 + -3x = -5 + 10x Solving -1 + -3x = -5 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -1 + -3x + -10x = -5 + 10x + -10x Combine like terms: -3x + -10x = -13x -1 + -13x = -5 + 10x + -10x Combine like terms: 10x + -10x = 0 -1 + -13x = -5 + 0 -1 + -13x = -5 Add '1' to each side of the equation. -1 + 1 + -13x = -5 + 1 Combine like terms: -1 + 1 = 0 0 + -13x = -5 + 1 -13x = -5 + 1 Combine like terms: -5 + 1 = -4 -13x = -4 Divide each side by '-13'. x = 0.3076923077 Simplifying x = 0.3076923077
| .8x=212 | | 115+8x=19 | | (4/3)*3.14*15^3 | | -5x+3(1-x)=1x+-2(1-x) | | (4/3)3.14*15^3 | | 5x+3(1-x)=1x+-2(1-x) | | 9x^3-10x^2-16x=0 | | 89x=2.14 | | -5-(x+2)=-5(1+x)+3 | | -4+3(x+4)=5 | | f(x)=750(0.25) | | -4x+1(1-x)=0x+-1(1-x) | | 2-6c-9+9c= | | 5(x-4)=-9(x+3)+41 | | 10/9=8/x | | 70x+20x=3300 | | 8x+5=-115 | | 1x+4(1-x)=4x+1(1-x) | | (3x^3-4x^4)2x^2= | | -5x+3(1-x)=-3x+1(1-x) | | 70s+20r=3300 | | 4/8=6/n | | 2(62.5+-2y)+4y=125 | | |3x-1/4|=2 | | 2x+0(1-x)=-5x+3(1-x) | | 15xy/35yz | | 9x^2-24x-1=0 | | 5x+-4(1-x)=2x+0(1-x) | | 10z^7(6z+3z^4+4)= | | 0=7x^3-24x^2-16x | | 4y+2x=125 | | 1.6*4= |